STRATEGI DIGITAL MARKETING MELALUI TIKTOK DALAM PERSPEKTIF ETIKA BISNIS SYARIAH: STUDI KASUS MINAT BELI KONSUMEN PADA UMKM ANA DIMSUM DI DESA CIDERUM, BOGOR - Abrori; Azizah Mursyidah; Bayu Purnama Putra; Hana Tri Supono; Nurfitri Candra Kirana (JURNAL KAJIAN ISLAM MODERN, 2026)
This study examines the influence of TikTok marketing content on consumer purchase intention for Ana Dimsum products in Ciderum Village, Bogor, amid the rapid growth of digital marketing trends. The research utilizes a quantitative cross-sectional method with a population of 50 respondents and a sample of 45 individuals. The research instrument consists of checklists measuring TikTok content variables and purchase intention. Descriptive analysis results show that 48,9% of respondents are TikTok users, and 44,4% express interest in Ana Dimsum products. Chi-square statistical testing yielded a p-value of 8,41 (α > 0,05), indicating a significant influence between TikTok content and purchase intention. The Odds Ratio (OR) of 724 demonstrates that TikTok users have a 724 times higher likelihood of purchasing "contemporary" dimsum compared to non-users. In conclusion, TikTok marketing effectively and significantly drives consumer purchase intention within the local community.Keywords: TikTok Marketing, Purchase Intention, MSMEs, Ana Dimsum.